A spectrophotometric study on the visual pigments from retinal photoreceptors of juvenile sutchi catfish Pangasianodon hypophthalmus - Nai, Han Tan; Mukai, Yukinori; Mohammad Noor, Normawaty; Okawa, Ryo; Anraku, Kazujiko (2016)
Visual pigments are photopigments in the retinal photoreceptors that absorb light and mediate vision. The absorbance spectra of visual pigments that fish has are closely re-lated to the environmental light in its natural habitats. In order to understand the visual spectral sensitivity of juvenile sutchi catfish (Pangasianodon hypophthalmus), the ab-sorbance spectra of visual pigments were measured in this study. Sutchi catfish juve-niles were dark-adapted overnight and then anaesthetized. In the dark room, both eyes of the juveniles were enucleated and retinae were isolated under a dissecting micro-scope with the aid of a night vision goggles. The retinae were cut into small pieces (~ 9 mm2) in a petri dish filled with buffered saline. Each retina sample was placed on a co-verslip with a drop of saline. Second smaller coverslip was then placed on the sample and sealed with Vaseline to prevent dryness. Absorbance measurement was conducted by means of spectrophotometrically using a portable spectrophotometer. The sample and baseline absorbance spectra were analysed using a custom-made software to obtain spectral absorbance curves of the measured visual pigments. The spectral absorbance curves obtained from measurements indicated parabolic shape. Higher absorbance was observed at the wavelength ranged from 530 nm to 580 nm. It is clearly suggested that the visual spectral sensitivity of juvenile sutchi catfish is adapted to longer wavelength of light which dominates in turbid water. The results will be useful in determining opti-mum light conditions to improve seed production of sutchi catfish as well as conserv-ing its natural population.